Comparative study of multidirectional pedestrian flows: Insights and dynamics - Karim, Rehmat; Weiguo, Song; Rasa, Abdul Rahim; Khan, Mujeeb Ali; Bilintoh, Nashiru Danniel (Physica A, 2024)
This study investigates multidirectional pedestrian flow by examining walking characteristics and behavioral factors impacting pedestrian dynamics. Parameters such as mean walking velocities, distance covered, and time taken by pedestrians were analyzed. Contrary to the expected inverse relationship between velocity and density, our findings revealed an increase in mean velocities in certain scenarios, attributed to conditions where the pedestrian density had not reached its maximum possible level and unpredicted pedestrian behaviors. Comparative analysis revealed that both Pakistani and Chinese pedestrians walk at nearly similar speeds. For instance, Pakistani pedestrians maintain a mean velocity of 1.36 ± 0.42 m/s at a density of 0.48 ped/m², while Chinese pedestrians maintain 1.27 ± 0.23 m/s at a density of 0.41 ped/m². Behavioral characteristics such as aggressive behavior, crowd avoidance, and waiting behavior were identified, with aggressive pedestrians exhibiting higher velocities than those avoiding crowds. A space-time diagram was utilized to categorize pedestrian flow types and behaviors, demonstrating increased stopping times with higher pedestrian numbers. Cultural factors, including side preferences, were analyzed using a binomial test, which returned a p-value of 0.968, indicating no significant preference for right-hand movement among Pakistani participants. These insights enhance the understanding of pedestrian dynamics and the influence of cultural norms on movement efficiency.